Is a safety guide wire necessary for transurethral lithotripsy using semi-rigid ureteroscope? Results from a prospective randomized controlled trial - Basiri, Abbas; de la Rosette, Jean J. M. C. H.; Hashemi, Milad Bonakdar; Shemshaki, Hamidreza; Zare, Ali; Borumandnia, Nasrin (Urology & Nephrology Research Center (UNRC), 2021)
Purpose: Experts recommend us to keep a safety guidewire during the process of upper urinary tract endoscopy, though there is a lack of high-level evidence to support the efficacy and safety of this opinion. This study was conducted to compare the outcome of ureteral stone breakage in the presence or absence of a safety guidewire. Materials and methods: Patients candidate for endoscopic breakage of ureteral stone using a semi-rigid ureteroscope, were randomly assigned in two groups based on keeping a safety guidewire (group1) or removing the guidewire (group2) before the process of breaking ureteral stone by lithoclast. Demographic factors, history of previous stone treatment, kidney function, stone location, symptoms duration and severity were recorded for each patient. Primary outcomes included success rate of stone treatment and secondary outcomes included number of attempts to enter to ureter, success rate of ureteral entry, success rate of stone achievement, stone migration rate and the success rate of ureteral stent insertion. The recorded data were entered to the SPSS software and descriptive statistical analysis including power calculation and non-inferiority design for the primary and secondary outcomes, was performed. P-value less than 0.05 was considered significant. Results: From January 2016 till May 2018, 320 patients were randomized with 160 patients in each arm. Considering the cases who were missed due to follow-up loss, there were 153 patients in group 1 and 147 patients in group 2 at the end of the study. Baseline data were equally distributed in both groups. Based on the initial analysis, the studied variables had no significant difference between two groups; though, according to the subgroup analysis of patients with proximal ureter stones, patients in Group 1 had higher rates of ureteral injury comparing to the patients in Group 2 (p = 0.03). Conclusion: According to our findings, keeping the safety guidewire through the process of endoscopic stone breakage (stone size: less than 1.5Cm) seems to add no significant benefit to the procedure outcome, while it increases the ureteral injuries in the proximal ureter stones, but not in mid or distal ureter stones.
Keywords: Ureteroscopy; Safety Guide Wire; Randomized Controlled Trial